1998
DOI: 10.2307/30143436
|View full text |Cite
|
Sign up to set email alerts
|

Low Risk for Tuberculosis in a Regional Pediatric Hospital: Nine-Year Study of Community Rates and the Mandatory Employee Tuberculin Skin-Test Program

Abstract: Despite intense active surveillance among thousands of hospital employees with >97% annual compliance, tuberculin conversion rates were low, and no cases of active TB were identified during 9 years of follow-up. There was no evidence of transmission of M tuberculosis from infected patients to employees during uncontrolled exposures. Rates of TB in the community were low. These data suggest that rigorous application of the Centers for Disease Control and Prevention guidelines and Occupation Safety and Health Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Several longitudinal studies have demonstrated a positive association between TST response and subsequent risk of active TB. 9,10 Randomized trials have shown that treatment of latent infection, diagnosed on the basis of positive TST, reduces the risk of active TB. This experimental evidence has lead to the policy of tuberculin testing and treatment of latent TB infection.…”
Section: Tuberculin Skin Testmentioning
confidence: 99%
“…Several longitudinal studies have demonstrated a positive association between TST response and subsequent risk of active TB. 9,10 Randomized trials have shown that treatment of latent infection, diagnosed on the basis of positive TST, reduces the risk of active TB. This experimental evidence has lead to the policy of tuberculin testing and treatment of latent TB infection.…”
Section: Tuberculin Skin Testmentioning
confidence: 99%
“…These data suggest that TB is a significant hazard for HCWs. By contrast, Christie et al 15 found low tuberculin conversion rates and only a 0.3% rate of active TB among HCWs with documented conversions during 9 years of follow-up in a pediatric hospital in Cincinnati, Ohio.…”
Section: Discussionmentioning
confidence: 86%
“…Although there is considerable evidence that workers who provide direct patient care are at greater risk for TB infection than workers who did not provide direct patient care [Mikol et al, 1952;Beck-Sagué et al, 1992;Dooley et al, 1992;Pearson et al, 1992;Zaza et al, 1995;Rullan et al, 1996;Boudreau et al, 1997;Behrman and Shofer, 1998], the results among studies are inconsistent. One explanation for the differences may be variation in the admission rates of TB patients [Bailey et al, 1995;Christie et al, 1998]. In institutions with fewer than 10 admissions for TB annually, the annual worker risk of infection was less than 0.2%, as compared to institutions such as the hospital we studied, with more than 200 admissions for TB annually and an annual worker infection rate between 1 and 10% [Menzies et al, 1995].…”
Section: Discussionmentioning
confidence: 95%